EVALUASI MANAJEMEN PENGELOLAAN OBAT TAHAP SELECTION DAN PROCUREMENT DI PUSKESMAS CEMPAKA PUTIH TAHUN 2018 - Mochammad Maulidie Alfiannor Saputera; Nabella Yunika Sari; Fatthul Jannah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
In the process of drug management management, the selection stage is a very decisive initial stage in drug planning where at this stage the selection of drugs is really needed for most disease patterns, which must refer to DOEN and FORNAS. Furthermore, the planning and procurement stages are carried out. This study aims to determine the suitability of drugs available with DOEN 2017 and FORNAS TK.1 2017 and the suitability of drug requests with drugs received at Cempaka Putih Public Health Center in 2018. This type of research is descriptive research by collecting case reports. The population in this study is RKO JKN & LPLPO data based on the APBD for the period December 2017-November 2018 and JKN for the period January-December 2018. The sampling technique is using saturated sampling technique. The instrument used in this study used an observation sheet. Based on the results of the study, the results of the suitability of drugs with APBD funds refer to DOEN (45.59%), and with FORNAS (49.04%), the suitability of drugs with JKN funds with Fornas (50%) and with DOEN (55.55%), suitability of drug demand and acceptance in LPLPO APBD (44.70%), suitability of drug demand and receipt at RKO JKN (28.12%).